UPAYA PENINGKATAN PARTISIPASI MASYARAKAT DALAM MENJAGA KUALITAS LINGKUNGAN OBJEK WISATA PANTAI BEROVA KABUPATEN KOLAKA UTARA - Risma Handayani (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2022)
Efforts to increase the participation of Community Objects in maintaining the environmental quality of Berova Beach Tourism, North Kolaka Regency. The main issues discussed are how these factors influence community perception and participation, the relationship between several factors that influence community participation in improving the environmental quality of the Berova beach tourism object. So with this problem the authors conducted research in the village of Pitulua. The method used is descriptive analysis which is carried out in accordance with the research objectives by clearly describing or describing what is in the field, while to study Efforts to Increase Participation in the Community Maintaining the Environmental Quality of the Berova Beach Tourism Object the method is used, namely Likert Scale Analysis and AHP. The results of the study show that factors that influence community participation, based on public perceptions, namely Cleanliness, Comfort and Safety and the most dominant influencing community participation is the Cleanliness factor in improving the environmental quality of the Berova tourist attraction. Keywords: Flood, Vulnerability and Mitigation.